Discourse on gender: A linguistic analysis of body autonomy and patriarchal narratives in Wa Ndiu-Diu - Ramis Rauf; Muhammad Fadli Muslimin; Afriani Ulya; Lucia Arter Lintang Gritantin (Studies in English Language and Education, 2025)
Wandiu-diu is a folktale from the Wolio community in Southeast Sulawesi, Indonesia, that depicts a family with two children, where the husband is a fisherman and the wife is a housewife. The husbands role is crucial, as his occupation and actions contribute to the construction of gender roles and power. This article argues that this folktale serves as a mechanism of control over womens bodies, underpinning patriarchal structures through three roles: married women, mothers, and independent women. Using Simone de Beauvoirs gender framework, this study categorizes the data into these three roles and analyzes relevant narratives from the tale. Beauvoirs gender theory critiques the Othering of women, highlighting their historical subordination to men in social, cultural, and political spheres. The findings reveal that Wandiu-dius transformation into a mermaid symbolizes patriarchal control over womens bodies. Marriage binds women to their husbands, motherhood renders them vulnerable through self-sacrifice, and seeking independence makes them objects of societal ridicule. The mermaid figure, rather than signifying freedom, eventually represents patriarchal constraints. Hence, the linguistic choices in Wandiu-diu reinforce patriarchal power, shaping portrayals of womens roles and struggles. Through lexical selection, narrative structure, and dialogue, the tale depicts women as subordinate, their autonomy met with resistance and punishment. Male speech, marked by imperative verbs and possessive pronouns, asserts dominance, while the mothers indirect speech reflects constrained autonomy. While appearing to symbolize female liberation, the tale eventually fortifies patriarchal oppression in the Wolio community of Southeast Sulawesi.